Socrates, or a Free Man in Communist Czechoslovakia - Firlej, Agata (Porównania, 2024)
The starting point for the research presented in this article is Jan Patočka's concept of two possible freedom attitudes towards the advantage of the totalitarian regime: Socratic (open confrontation) and Platonic (internal emigration). The first, radical way of practicing freedom was described based on the fate of selected figures of Czechoslovak culture: Jan Patočka, Jiřy Nĕmec and Eva Kantůrková, whose uncompromising decisions exposed them to death, exile or imprisonment. The three most important ideas that guided the heroes of the article will be indicated: truth, spirituality and will. In conclusion the parallel between the situation of Czechoslovak and Ukrainian is showed on the basis of the interest into the Socrates’ attitude, which is to be found in Oleksandr Boychenko’s articles.